2022
DOI: 10.3390/ma15196832
|View full text |Cite
|
Sign up to set email alerts
|

Fe(III) and Cu(II) Complexes of Chlorogenic Acid: Spectroscopic, Thermal, Anti-/Pro-Oxidant, and Cytotoxic Studies

Abstract: Complexes of chlorogenic acid (5-CQA) with copper(II) and iron(III) were synthesized in a solid state and examined by means of FT-IR, thermogravimetric, and elemental analyses. The molar stoichiometric ratios of metal:ligand for the solid forms of the complexes were established as Cu(II):L = 1:2 and Fe(III):L = 2:3 (L: 5-CQA), with the possible coordination through the carboxylate group and the hydroxyl group from the catechol moiety. In an aqueous solution at pH = 7.4, the composition of the complexes was Cu(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…The formation of Cu(II) complexes with catecholamines in aqueous solutions has already been already reported in 1979 by Fazakerley et al [18]. Catechol-containing Cu(II) complexes are still extensively studied due to their interesting properties [19][20][21]. In this paper, the authors, for the first time, propose the reduction of Cu(II) to Cu(I) following the interaction of cupric ions with catecholamines.…”
Section: Interaction Of Catecholamines With Cu(ii): a Uv-vis And Epr ...mentioning
confidence: 57%
“…The formation of Cu(II) complexes with catecholamines in aqueous solutions has already been already reported in 1979 by Fazakerley et al [18]. Catechol-containing Cu(II) complexes are still extensively studied due to their interesting properties [19][20][21]. In this paper, the authors, for the first time, propose the reduction of Cu(II) to Cu(I) following the interaction of cupric ions with catecholamines.…”
Section: Interaction Of Catecholamines With Cu(ii): a Uv-vis And Epr ...mentioning
confidence: 57%
“…5-CQA main cytotoxic effects on cancer cells are triggering apoptosis, suppressing cell proliferation, or inhibiting the cell cycle. Studies show ( S2 Table ) lack of cytotoxicity of 5-CQA towards HaCaT cell line in concentration range of 0.15–1000 nM [ 5 ], HL-60 and Jurkat cells in concentrations of 1–100 μM [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Chlorogenic acid (5-CQA) (S2 Fig) [4], an ester of caffeic acid and (−)-quinic acid, one of the most abundant phenolic acids, is widely distributed in fruits and vegetables like: apples, pears, carrots, or potatoes. Additionally, it can be found in most consumed beverages in the world: wine, tea and coffee [5][6][7]. Notably, chlorogenic acid demonstrates antimicrobial activity against bacteria (S1 Table ) like Gram-negative Escherichia coli (MIC 7.06 mg/mL) [8], Gram-positive Alicyclobacillus acidoterrestris (MIC 2 μg/mL) [9] and fungi Candida albicans with MIC (80 μg/mL) [10].…”
Section: Introductionmentioning
confidence: 99%
“…Caffeic acid and 5-caffeoylquinic acid generally form equimolar complexes with ferric iron [29]. Another study showed that complexes formed by two ferric irons and three 5-caffeoylqinic acid molecules or one Cu-ion and two 5 caffeoylquinic acid molecules are possible [117].…”
Section: Interactions Of Standards Applied To Dietary Supplementsmentioning
confidence: 99%